The Effect of Bioactivator Variation and Doses of Cow Dung on Quality of Coffee Exocarp Waste - Krismawati, Amik; Sugiono, Sugiono (El-Hayah : Jurnal Biologi, 2019)
Coffee exocarp waste produced from the harvest can be used as raw material for compost. The composting can be added with other ingredients to add organic material. Cow manure is the one ingredient that can be added to enrich organic materials. In the composting process, the time required will be longer, but the time can be accelerated by adding a bio activator. The finished compost can be applied at the plant to meet crop nutrient elements. The purpose of this research was to determine the effect of bio activator variation and doses of cow manure on the quality of compost from coffee exocarp waste. This research was conducted at compost house of Assessment Institute for Agricultural Technology (AIAT) and was held on February - April 2017. This research used factorial Randomized Block Design (RBD) with two factors; there is a variation of bio activator and doses of cow manure with three replication. Total number of treatment this research were 12 treatment, there are D1S1 = EM4 + 2 kg cow manure ; D2S1 = Moebillin + 2 kg cow manure; Petrofast + 2 kg cow manure; Decoprima + 2 kg cow manure; D1S2 = EM4 + 4 kg cow manure; D2S2 = Moebillin + 4 kg cow manure; D3S2 = Petrofast + 4 kg cow manure; D4S2 = Decoprima + 4 kg cow manure; D1S3: EM4 + 6 kg cow manure; D2S3 = Moebillin + 6 kg cow manure; D3S3 = Petrofast + 6 kg cow manure; D4S3 = Decoprima + 6 kg cow manure. The data obtained will be processed usingÂ Analysis of VarianceÂ (ANOVA). If there is a real effect, it will be continued using the BNT test (Least Significant Differences/LSD) with a 5% level. The Results showed the application of bio activator Decoprima (D4) and a dose of 6 kg cow manure (S3) could increase and shows the highest value of pH compost 6,01 (D4) and 6,06 (S3). The dose of 2 kg cow manure (S1) showed the highest compost shrinkage value (34.64%) compared to the 4 kg dose cow manure (S2) (32,22%) and 6 kg (S3) (25,68%). On the other hand, the application of bio activator variation and doses of cow manure did not significantly affect the quality of compost, including N-total (2,15% -2,60%), C-organic (21,40% -24,91%) and C/N ratio (8,81-11,15). The physical properties of the aroma compost show the smell of soil, and the color of the compost is dark brown.Â